Adapting to changes in climate and implementing mitigation measures - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The main objective of this brochure is to learn more about CCAFS activities and results in Nicaragua and potential future work through three farms in Matagalpa department. These farms were selected because joint projects developed by CIAT/CCAFS, local organizations such as CECOCAFEN Cooperative (Group of Cooperatives of Matagalpa) and other partners such as Catholic Relief Services (CRS) have had a positive incidence in the agricultural practices of these farms. The brochure will allow discovering and evidencing how farmers are being beneficiated from collaborative research, and most of all, how farmers are reducing their food insecurity at the same time that they are adapting to changes in climate and implementing mitigation measures.